SiGe and CMOS Technology for State-of-the-Art Millimeter-Wave Transceivers - Du Preez, Jaco; Sinha, Saurabh; Sengupta, Kaushik (IEEE access, 2023)
Innovation and evolution are paramount where the demand for wideband, data-intensive connectivity is ever-increasing, and the only constant is change. Standards that define the operation of next-generation mobile networks are moving away from the traditional radio frequency (RF) spectrum and into millimeter-wave (mm-wave) bands. The physical layer (PHY) for IEEE 802.11ad Wi-Fi and 802.11ay WLANs dictates operation in the unlicensed 60 GHz band. 5G New Radio (NR) applications utilize selected bands from 26 to 39 GHz. Additionally, newly developing Fourth Industrial Revolution (4IR) applications depend on 5G NR as an enabling technology. Satellite communications and wireless backhaul will occur in E-band between 70-86 GHz. Increasing demands from the market cause designers to push boundaries, and the development of standards guide technological advances. Perhaps the most substantial improvements are observed in integrated circuit technology. This article details the major Si processes, namely Complementary Metal Oxide Semiconductor (CMOS) and SiGe Bipolar CMOS (BiCMOS), and their foray into the wireless transceiver space traditionally dominated by GaAs. CMOS and BiCMOS have become popular in many communities because of their low fabrication cost and excellent digital integration capabilities. RF performance has matured to where Si is a serious competitor for tried-and-tested III-V technologies. Some extreme environments and sophisticated applications still favor GaAs and GaN, however. GaAs, for example, can yield unparalleled output power and excellent noise figure performance, albeit at a higher cost and increased design and manufacturing complexity due to the multi-chip nature of these circuits.